O-018 Magnetically Assisted Remote-controlled Endovascular Catheter for Interventional MRI: In Vitro Navigation at 1.5 T versus X-ray Fluoroscopy. (26th July 2014) - Hetts, S; Losey, A; Lillaney, P; Cooke, D; Thorne, B; Saeed, M; Arenson, R; Wilson, M
Abstract : Purpose: To advance the field of endovascular interventional MRI, which could allow real-time assessment of brain tissue viability during acute ischemic stroke interventions, we have developed a prototype MRI compatible magnetically assisted remote controlled catheter (MARC). We sought to compare navigation of a MARC catheter under real-time MRI with manual navigation under MRI and standard x-ray guidance in endovascular catheterization procedures in vitro . Materials and Methods: A custom clinical-grade micro catheter prototype with a solenoid coil at the distal tip was deflected with a foot pedal actuator used to deliver current of 300 mA. Investigators navigated the catheter into branch vessels in a cryogel abdominal aortic phantom. This was repeated under MR imaging guidance without magnetic assistance and under conventional x-ray fluoroscopy. MR experiments were performed at 1.5T using a balanced steady-state free precession sequence. The mean procedure times and percentage catheterization success data were determined and analyzed with a linear mixed-effects regression analysis. Results: The catheter was clearly visible under real-time MRI. One hundred ninety-two (80%) of 240 turns were successfully completed with magnetically assisted guidance versus 144 (60%) of 240 turns with non-assisted guidance (P = 0.001) and 119 (74%) of 160 turns with standard X-ray guidance (P = 0.028). Mean procedure time was shorter with magnetically assisted than with non-assisted guidance under MRI (37 seconds vs 55 seconds, P = 0.001), and time was similar between magnetically assisted and standard x-ray guidance (37 seconds vs 44 seconds, P = 0.045). When stratified by angle of branch vessel, magnetic assistance was faster than nonassisted MRI guidance at turns of 45°, 60°, and 75°. Conclusion: In this study, a MARC catheter for endovascular navigation under real-time MRI guidance was developed and tested. For catheterization of branch vessels arising at large angles, magnetically assisted catheterization was faster than manual catheterization under MR imaging guidance and was comparable to standard x-ray guidance. This represents a significant advance in MRI guided catheterization and brings the performance of MRI guided stroke interventions closer to clinical reality. Disclosures: S. Hetts: 1; C; NIH-NIBIB, NIH-NCI, Siemens, Covidien. 2; C; Stryker, Penumbra, Silk Road Medical, Medina Medical. 4; C; Medina Medical, ChemoFilter. A. Losey: None. P. Lillaney: None. D. Cooke: 1; C; Siemens. 4; C; Viket. B. Thorne: None. M. Saeed: None. R. Arenson: None. M. Wilson: None.